Patterns of care in Jehovah's Witnesses patients with solid tumours and lymphoma. Issue 2 (26th October 2018) - Chang Lee, Rachael; Sukumaran, Shawgi; Koczwara, Bogda; Woodman, Richard; Kichenadasse, Ganessan; Roy, Amitesh; Vatandoust, Sina; Karapetis, Chris
Abstract: Background: Supportive care of Jehovah's Witnesses (JWs) diagnosed with cancer can be challenging, as they do not accept red blood cell (RBC) transfusions. Aim: The study was designed to determine treatment preferences and pattern of care offered to JWs diagnosed with cancer and its impact on cancer management. Methods and results: A retrospective cohort study of JWs with solid malignancies or lymphoma in our institution between 2005 and 2015 was conducted. Survival statistics were estimated using Kaplan Meier survival curves and Cox proportional regression model. A total of 63 JWs were identified with a median age of 70 years. At diagnosis, 34% ( n = 22) had anaemia. All 63 declined RBC transfusion, including 19 patients who later developed transfusion threshold during anti‐cancer treatment. Forty‐three percent ( n = 27) JWs had advanced (stage 4) disease, and 76% ( n = 48) had Eastern Cooperative Oncology Group of 0 to 1. JWs were willing to accept surgery and radiation rather than chemotherapy. Treatment was deemed to be suboptimal in 22% ( n = 14) JWs due to early treatment discontinuation, administration of non‐standard chemotherapy regimen, or dose reduction due to anaemia and denial of blood transfusion. Twenty‐seven percent ( n = 17) received hematopoietic growth factors (erythropoiesis‐stimulating agents and pegfilgrastim). There was no mortality directly attributed to anaemia or refusal of blood transfusion in the entire cohort. Conclusion: Jehovah's Witnesses declined RBC transfusion at diagnosis and during cancer therapy even if medically indicated. Management pathways need to be prospectively defined for this group of patients.